On copper removal from aquatic media using simultaneous and sequential iron-perlite composites. (April 2021) - Khudr, Mouhammad Shadi; Ibrahim, Yassin Mohamed Elhassan; Garforth, Arthur; Alfutimie, Abdullatif
Graphical abstract: Highlights: This work combines adsorption by perlite and disposition by Fe to extract Cu 2+ . The combination efficiency depends on how and when these constituents are applied. A concurrent, compared to sequential, separate combo led to rapid Cu 2+ extraction. Fast uptake of Cu 2+ under the concurrent application was 50 % at 15 min, and reached 71 % at 120 min. This suggests an additive effect of the iron-perlite combination larger than each constituent's effect. Abstract: The use of affordable and inert adsorbents to mitigate copper pollution, with a lesser burden on the environment, is desirable. However, aiding the adsorption process of a promising adsorbent, e.g. expanded volcanic glass (perlite), with a reducing companion, e.g. solid iron, that can displace and dispose of copper from polluted water has never been tested before. In this laboratory study, we investigated the removal of Cu 2+, resulting from contaminating freshwater with copper sulphate pentahydrate, using simultaneous or non-simultaneous (sequential) mixes of expanded perlite and iron coarse powder over 23 h. The percentage of copper removal was calculated over time using induced coupled plasma (ICP-OES). A rapid removal of 71 % at 120 min was achieved when the perlite and iron were added simultaneously in separate permeable pouches; the application of the iron after the perlite led to 78 % of removal at 1380 min that was almost identical to what was accrued under perlite alone (77 %). This, therefore, suggests that the presence of iron is most advantageous in the short run as it leads to fast uptake of Cu 2+, attributable to the combined action of the reduction of Cu 2+ by iron and Cu 2+ adsorption by perlite. Further investigation was carried out using Energy-Dispersive X-Ray Spectroscopy (EDAX), X-Ray Diffraction (XRD), Brunauer, Emmett and Teller (BET), and Fourier-Transform Infrared Spectroscopy (FTIR). This multidisciplinary work provides insights and mechanisms for prompt heavy metal removal using novel time-specific metal-adsorbent combinations and thus merits wider testing across different classes of adsorbents, pollutants, and water systems.